Note on Isomorphism Theorems of Hyperrings - Muthusamy Velrajan; Arjunan Asokkumar (International Journal of Mathematics and Mathematical Sciences)
There are different notions of hyperrings (𝑅,+,⋅). In this paper, we extend the isomorphism theorems to hyperrings, where the additions and the multiplications are hyperoperations.